The mistake made by the student is in the distribution of the negative signs. To simplify the expression correctly, we use the property that i^2 is equal to -1.
(-3i)(-5i)
= -3(-5) * i * i
= 15 * i^2
= 15 * (-1) [Substituting i^2 with -1]
= -15
So, the correct simplification of the expression is -15.
a student has simplified the following expression incorrectly
identify the mistake that was made and simply the ex;ression correctly show all necessary steps
(-3i)(-5i)
15i was the studentts answer
1 answer